Physical Studies on Isolated Human Prothrombin Fragment-2. Comparisons with Human Prothrombin Fragment-1 - Schaefer, Daniel J; Scott, Mary E; Gabriel, Don A; Gerth, Jean L; Aronson, David L; Hiskey, Richard G; Koehler, Karl A (Thrombosis and Haemostasis, 1979)
Variation of pH strongly affects the fluorescence intensity of human prothrombin fragment-1 in a manner suggesting contributions from a number of protropic equilibria including groups with apparent pKa values near 3.0. These results suggest a structural role for pKa1 of γ-carboxyglutamic acid moieties. Added calcium ions (9 mM calcium chloride) quench the fluorescence titration curve.uniformly above pH 4. Below pH 4, however, the titration curve in the presence of calcium ions suggests that calcium-ion-dependent processes leading to fluorescence quenching are pH-dependent. Upon back titration of human fragment-1, from pH 9, hysteresis is observed.Human prothrombin fragment-2 fluorescence titration curves are relatively broad at low pH suggesting the titration of normal carboxyl groups. The titration curves of fragment-2 are not affected by the presence of calcium ions, and hysteresis occurs upon back titration from low pH values. Circular dichroism (CD) Cotton effects appear at 232 nm and 280 nm and a trough appears at 203 nm in the CD spectrum of human prothrombin fragment-2. The Cotton effects in the region from 230 nm to 300 nm are sensitive to pH, ellipticity values at 232 nm increasing from approximately 300 at pH 2.5 to 1300 (degree-cm/decimole) at neutral pH and finally become negative at high pH values. In contrast to fragment-1, at neutral pH the fragment-2 Cotton effect at 232 nm is insensitive to the presence of 8 mM calcium chloride.